2017
DOI: 10.1159/000456671
|View full text |Cite
|
Sign up to set email alerts
|

Transbronchial Lung Cryobiopsy in Diffuse Parenchymal Lung Disease: Comparison between Biopsy from 1 Segment and Biopsy from 2 Segments - Diagnostic Yield and Complications

Abstract: Background: Transbronchial lung cryobiopsy is an innovative method of obtaining samples from the parenchyma of patients with diffuse parenchymal lung diseases. However, the technique is not yet standardized, and uncertainty exists about the optimal protocol, including the number of samples, the biopsy size, and the choice of the biopsy site. Objectives: To compare the diagnostic yield and complications of cryobiopsy with different strategies adopted to sample lung tissue (number of samples, biopsy site, and sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
85
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(101 citation statements)
references
References 36 publications
7
85
0
Order By: Relevance
“…Although there is a debate which areas should be chosen for TBLC, it seems reasonable to target different lung areas, more affected areas, and areas with different radiological patterns. This goes along with Ravaglia et al [16] who found that taking biopsies from a different segment of the same lobe instead of biopsies from one segment rose the diagnostic yield from 69 to 96%. However, taking biopsies only from areas suspicious for pure fibrotic changes on HRCT is unlikely to provide specific histological changes and should therefore be avoided.…”
Section: Tblc: the Proceduressupporting
confidence: 59%
“…Although there is a debate which areas should be chosen for TBLC, it seems reasonable to target different lung areas, more affected areas, and areas with different radiological patterns. This goes along with Ravaglia et al [16] who found that taking biopsies from a different segment of the same lobe instead of biopsies from one segment rose the diagnostic yield from 69 to 96%. However, taking biopsies only from areas suspicious for pure fibrotic changes on HRCT is unlikely to provide specific histological changes and should therefore be avoided.…”
Section: Tblc: the Proceduressupporting
confidence: 59%
“…The NSIP or DIP patterns or other rarer and complicated lesions have also been identified in samples obtained by cryoprobes, although in a limited number of cases [52,53]. Thus, data on the clinical meaning of NSIP/DIP and other patterns on cryobiopsy have not been assessed yet.…”
Section: Pathological Considerationsmentioning
confidence: 99%
“…Therefore, the optimal number of biopsies cannot be uniformly established, although in the majority of centers 3-5 biopsies are usually taken. However, a recent study suggested that biopsies from different segments within the same lobe are associated with a higher diagnostic yield compared to biopsies in the same segment [53]. Multiple biopsies are usually undertaken in an effort to reduce sampling error, but data on the different strategies adopted to sample lung tissue are still missing in the literature; no prospective studies have been published yet in terms of diagnostic yield and rates of complications.…”
Section: How Many Cryobiopsies Should Be Obtained?mentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnostic sensitivity of TLCB has been compared with forceps biopsy (FB), showing a better diagnostic yield in several studies [1][2][3][4] . Samples obtained by TLCB are of larger size than those of FB and lack the mechanical crush artifacts, improving the quality of the histopathology sample [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%